Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/molecules22112009
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Aggregation-Induced Emission by Introducing Multiple o-Carborane Substitutions into Triphenylamine

Abstract: The enhancement of aggregation-induced emission (AIE) is presented on the basis of the strategy for improving solid-state luminescence by employing multiple o-carborane substituents. We synthesized the modified triphenylamines with various numbers of o-carborane units and compared their optical properties. From the optical measurements, the emission bands from the twisted intramolecular charge transfer (TICT) state were obtained from the modified triphenylamines. It was notable that emission efficiencies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 55 publications
0
17
0
1
Order By: Relevance
“…The intense blue fluorescent emission of compound 1 can be assigned to the local excited-state emission of a Cz-phenylacetylene fragment (Li et al, 2019), and the solvatochromic shift of 2 suggested the intramolecular charge-transfer (ICT) behavior between Cb and Cz units (Wee et al, 2012a; Nghia et al, 2018b). The temperature dependency of emission of 2 was also investigated (Figure S10), the results showed that the fluorescence intensity of 2 slightly decreased when temperature rises, implying that the emission band at around 348 nm was from twisted-ICT state, whose emission effect could be affected by environment conditions such as polarity of solvent and temperature (Nishino et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The intense blue fluorescent emission of compound 1 can be assigned to the local excited-state emission of a Cz-phenylacetylene fragment (Li et al, 2019), and the solvatochromic shift of 2 suggested the intramolecular charge-transfer (ICT) behavior between Cb and Cz units (Wee et al, 2012a; Nghia et al, 2018b). The temperature dependency of emission of 2 was also investigated (Figure S10), the results showed that the fluorescence intensity of 2 slightly decreased when temperature rises, implying that the emission band at around 348 nm was from twisted-ICT state, whose emission effect could be affected by environment conditions such as polarity of solvent and temperature (Nishino et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of this unit to an aryl group leads to the formation of a donor-acceptor conjugated system owing to the strongly electron-withdrawing C atoms and highly delocalized 3D aromaticity of the o -carborane cage. Such a good conjugated system results in intramolecular charge transfer (ICT) transition between the two components [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. Thus, the unprecedented luminescent properties of numerous o -carboranyl compounds emerge from the ICT-based emissive features [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon depends on the dihedral angle between the diazaboryl moiety and C–C bond of o -carborane. In addition, various fluorophores possessing o -carboranyl groups have exhibited multiple photoluminescence (PL) originating from the alternation of the twisted ICT state [43,44,45,46,47,48,49,50,51]. These results clearly indicate that structural features can play an important role in controlling the intrinsic photophysical and electronic characteristics of o -carboranyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these desirable electronic properties are due to the unique characteristics of the o -carborane unit, such as its strongly electron-deficient nature, as well as its highly polarizable σ-aromaticity. In addition, these properties facilitate the formation of various donor‒acceptor systems, leading to intriguing intramolecular charge-transfer (ICT) transitions between numerous π -conjugated aromatic groups and o -carborane cages [29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Hence, these features have become ultimate sources for generating specific luminescence behavior in a variety of o -carborane-based compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are the results of changes in the molecular structure and the regulation of the free rotations of the aromatic groups bound to the o -carboranyl units. In addition, various o -carborane-containing donor-acceptor systems exhibit intriguing photophysical properties through twisted intramolecular charge-transfer (TICT) processes [43,44,45,46,47,48,49,50,51,52,53]. Along with these previous studies, our group reported significant changes in radiative ICT mechanisms by modulating the planarities of several phenylene groups that were substituted on o -carborane cages [60,61,62].…”
Section: Introductionmentioning
confidence: 99%